A structural basis for bacterial evasion of antibody responses through inhibitory receptor targeting - Zhang, Ying (My University, 2025)
Group B Streptococcus (GBS; Streptococcus agalactiae) continues to be a primary cause of neonatal sepsis while also representing a significant pathogen among immunocompromised adults. This work reveals the structural basis behind a new GBS immune-evasion mechanism whereby the cell-wall–anchored [beta] protein (~130 kDa) interacts with human inhibitory receptors to diminish antibody-mediated effector responses. The [beta] protein functions as a ligand for leukocyte immunoglobulin-like receptor B3 (LILRB3) an ITIM-containing inhibitory receptor found on human myeloid cells that dampens Fc receptor–driven activation. Our observations provide a framework for defining the molecular-level details underpinning the [beta]-LILRB3 interaction and using this information to probe its functional consequences. Domain mapping combined with surface plasmon resonance experiments uncovered two separate regions within the [beta] protein B6C (residues 226-391) and B75KN (residues 504-789) that serve as independent LILRB3-binding domains, with both displaying nanomolar binding affinities. The B6C crystal structure, resolved to 2.05 Å, unveiled an extended four-helix bundle configuration spanning ~111 Å, which differed substantially from existing computational models. Solution structures of both B6C/LILRB3 and B75KN-CTD/LILRB3 complexes were characterized using small-angle X-ray scattering with size-exclusion chromatography (SEC-SAXS), demonstrating that each domain recognizes the D3-D4 region of LILRB3. Mutagenesis experiments based on structural insights pinpointed essential interface residues: K332 and R336 within B6C, along with L721, D722, and F740 in B75KN-CTD. These mutations selectively eliminated LILRB3 binding yet maintained interactions with additional host proteins such as complement Factor H. Analysis of the ternary complex via SEC-SAXS showed that individual [beta] protein molecules engage two LILRB3 ectodomains concurrently, establishing a 1:2 stoichiometry that facilitates receptor cross-linking. Investigation of biological consequences demonstrated that [beta] protein-induced LILRB3 clustering inhibits antibody-mediated neutrophil activation and bacterial killing, thereby promoting bacterial persistence. This mechanism exhibits species specificity, as the [beta] protein cannot bind the murine ortholog PIR-B. Additionally, naturally existing LILRB3 variants within the D3-D4 domain entirely abolished [beta] protein recognition, indicating that host genetic diversity could modulate GBS infection outcomes. In summary, we provide the initial structural descriptions of a mechanism used by a prominent bacterial pathogen to exploit human inhibitory receptors and thereby overcome antibody-based immunity. Uncovering this new virulence mechanism advances our comprehension of GBS pathogenesis and offers potential avenues for innovative therapeutic strategies. It also provides a rationale for investigating similar evasion mechanisms in diverse host/pathogen interactions.
Keywords: Immune evasion; Group B Streptococcus; Leukocyte immunoglobulin-like receptor B3; Neutrophil